HUBUNGAN MOTIVASI KERJA DENGAN PENGGUNAAN ELECTRONIC MEDICAL RECORDS (ERM) PADA PERAWAT DI RUANG RAWAT INAP RSUD DR. SOEGIRI LAMONGAN - Alisahyan, Nur Safirani; Suratmi; Qowi , Nurul Hikmatul (Jurnal Keperawatan Muhammadiyah, 2025)
Electronic Medical Records (EMR) present a major challenge for nurses in managing various administrative and technical demands, often leading to difficulties in documentation. These challenges can be addressed by improving work motivation and the quality of healthcare services. This study aimed to analyze the relationship between work motivation and the use of Electronic Medical Records (EMR) among nurses. An analytic correlational study with a cross-sectional approach was employed. The sample consisted of 117 nurses selected through cluster random sampling. Data were collected using questionnaires and analyzed using the Spearman rho test via SPSS software. The results showed that the majority of nurses had high work motivation (72 nurses, 61.5%), and most classified their EMR use as moderate (63 nurses, 53.8%). Statistical analysis indicated a significant positive correlation between work motivation and EMR usage (p = 0.000; rs = 0.065), suggesting a strong positive association between these variables among nurses in the inpatient ward of Dr. Soegiri Regional Public Hospital, Lamongan. Based on these findings, it can be concluded that most nurses demonstrated high work motivation while EMR usage remained moderate. This research may serve as a valuable reference in developing strategies to enhance nursing service quality through optimal and sustainable use of technology.